Determination of polycyclic aromatic hydrocarbon (PAH) contents in micro-volumes of the whole blood and liver of Red Kite by a simplified GC-MS/MS method. Issue 4 (16th March 2022) - Morin-Crini, Nadia; Scheifler, Renaud; Amiot, Caroline; Riols, Romain; Coeurdassier, Michael
ABSTRACT: The aim of this work was to determine PAH concentrations in two matrices, fluid samples and biological tissue, from Red Kite. For this purpose, a simplified and sensitive method for the analysis of 16 PAHs at trace levels in small samples of whole blood and liver was developed and validated using dispersive extraction in n-hexane combined with gas chromatography-triple quadrupole mass spectrometry (GC-MS/MS). For blood and liver, the average limits of detection were 0.71 ng mL −1 and 3.16 ng g −1, the mean relative standard deviations (RSD (%)) were 16% and 15%, and the mean relative recoveries were 100% and 92% for all PAH compounds, respectively. This method was applied to PAH determination in the liver and blood of Red kites from wild populations. At least one PAH was detected in the blood and in the liver of 83% and 62% of the individual birds, respectively. Acenaphthene, anthracene and phenanthrene were the most frequently detected in the blood, while the blood concentrations of naphthalene, phenanthrene and pyrene were the highest. In the liver, fluoranthene was detected in 54% of the individual birds, followed by naphthalene, fluoranthene, phenanthrene and benzo[k]fluoranthene, with the highest concentrations being those of naphthalene and phenanthrene. This demonstrated that our method is suitable for assessing trace levels of PAHs in red kite blood and tissue and monitoring exposure in their natural environment. Moreover, our data show that raptors may be exposed to a mixture of PAHs, among which some belong to the IARC carcinogen classes for humans 1 and 2B, throughout their life cycle.